2020
DOI: 10.1109/lra.2020.3010461
|View full text |Cite
|
Sign up to set email alerts
|

Deep Reinforcement Learning for Tactile Robotics: Learning to Type on a Braille Keyboard

Abstract: Artificial touch would seem well-suited for Reinforcement Learning (RL), since both paradigms rely on interaction with an environment. Here we propose a new environment and set of tasks to encourage development of tactile reinforcement learning: learning to type on a braille keyboard. Four tasks are proposed, progressing in difficulty from arrow to alphabet keys and from discrete to continuous actions. A simulated counterpart is also constructed by sampling tactile data from the physical environment. Using sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 24 publications
0
27
0
Order By: Relevance
“…SoftBOT hands (middle row): tactile Model-M2 [69], tactile Model-GR2 [71], tactile Model-O [50], tactile Shadow Modular Grasper [74] and tactile SoftHand [30]. SoftBOT systems (bottom row): 3D-printed TacTip on ABB robot arm for tactile servo control [46], [77], TacTip on UR5 arm for reinforcement learning [75], TacFoot on walking robot [76], tactile Model-O on UR5 robot arm for grasping and slip detection [36], [50] and tacWhisker mounted on ABB robot arm [73].…”
Section: A 3d-printed Tactip and Integration Into Robot Handsmentioning
confidence: 99%
See 2 more Smart Citations
“…SoftBOT hands (middle row): tactile Model-M2 [69], tactile Model-GR2 [71], tactile Model-O [50], tactile Shadow Modular Grasper [74] and tactile SoftHand [30]. SoftBOT systems (bottom row): 3D-printed TacTip on ABB robot arm for tactile servo control [46], [77], TacTip on UR5 arm for reinforcement learning [75], TacFoot on walking robot [76], tactile Model-O on UR5 robot arm for grasping and slip detection [36], [50] and tacWhisker mounted on ABB robot arm [73].…”
Section: A 3d-printed Tactip and Integration Into Robot Handsmentioning
confidence: 99%
“…New tactile capabilities developed with the TacTip include: (a) pose-based servo control, where a tactile fingertip mounted on a robot arm slides delicately over unknown complex 3D objects (Figure 5a; [77], [86], [87]); (b) pushing manipulation of unknown objects using only tactile sensing and proprioceptive knowledge of where the sensor is positioned relative to a goal location (Figure 5b; [88]); (c) acquiring the novel skill of single-fingered typing on a braille keyboard, learning the identity of keys and how to navigate the keyboard from touch (Figure 5c [86], [87] tactile & proprioceptive feedback [88] Learning to type Braille [75] (d) Object & grasp-success prediction (e) In-hand tactile manipulation (f) Fine control of contact with an underactuated tactile hand [50] for fully-actuated stable grasping with an anthropomorphic tactile hand For all examples, the use of convolutional neural networks was critical for the tactile capability to be reached. configuration with a fully-actuated tactile Shadow Modular Grasper (Figure 5e; [84]); (f) fine control of contact onto unknown objects placed in-hand using an anthropomorphic tactile hand based on the Pisa/IIT SoftHand (Figure 5f; [30]).…”
Section: Period III (2019-): Deep Learning With the Tactipmentioning
confidence: 99%
See 1 more Smart Citation
“…First, under the constraints of the discrete action space and training in a real-world setting, Rainbow [23] was applied (Figure 1a). Rainbow integrating Deep Q-Networks (DQN) [14] with recent advancements [24]- [28] in reinforcement learning has demonstrated outstanding performance in real world environments [29]. Replay memory [14], a representative an off-policy method to enhance sample efficiency and increase the training speed with quality data, was a key component to reduce the physical time requirement.…”
Section: Introductionmentioning
confidence: 99%
“…The authors showed how the learning of tactile feedback can be made more efficient by reducing the dimensionality of the tactile information through spectral clustering and principal component analysis. Another study Church et al (2020) presented a challenging tactile robotics environment for learning to type on a braille keyboard with deep reinforcement learning algorithms. Preliminary results showed that successful learning can take place directly on a physical robot equipped with a biometric tactile sensor.…”
Section: Introductionmentioning
confidence: 99%